Revision of the genus Jethsura Cameron, 1902 (Hymenoptera: Ichneumonidae: Ichneumoninae: Phaeogenini) - Claridge, Brandon (Zootaxa, 2021)
The genus Jethsura Cameron is revised. Jethsura euthenia sp. nov., Jethsura gondawindua sp. nov., and Jethsura serpentina sp. nov. are newly described from Colombia, and Jethsura rubricauda sp. nov. is described from Mexico. Jethsura pyriformis (Provancher) from the Nearctic region is redescribed. Species images, distribution maps and an illustrated key is provided.